Hydrogen-induced failure of TiNi based alloy with coarse-grained and ultrafine-grained structure; Procedia Structural Integrity; Vol. 2: 21st European Conference on Fracture: ECF21, 20-24 June 2016, Catania, Italy - Baturin A. A. Anatoly Anatolievich; Lotkov A. I. Aleksandr Ivanovich; Grishkov V. N. Viktor Nikolaevich; Rodionov I. S. Ivan Sergeevich; Krukovsky K. V. Konstantin Vitaljevich (2016, 2016)
Title screen